2012
DOI: 10.1093/glycob/cws083
|View full text |Cite
|
Sign up to set email alerts
|

Detailed O-glycomics of the Muc2 mucin from colon of wild-type, core 1- and core 3-transferase-deficient mice highlights differences compared with human MUC2

Abstract: The heavily O-glycosylated mucin MUC2 constitutes the major protein in the mucosal layer that acts as a physical barrier protecting the epithelial layer in the colon. In this study, Muc2 was purified from mucosal scrapings from the colon of wild-type (WT) mice, core 3 transferase knockout (C3Gnt(-/-)) mice and intestinal epithelial cell-specific core 1 knockout (IEC C1Galt1(-/-)) mice. The Muc2 O-glycans were released by reductive β-elimination and analyzed with liquid chromatography-mass spectrometry in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 40 publications
4
78
2
Order By: Relevance
“…MUC2 alone is coated with over 100 different O-linked glycan structures in humans 58 . These glycans differ between mice and humans 59 , and differences in complex glycan “preference” by various bacterial species is a suggested mechanism of host-specific selection of a characteristic microbiome profile. In agreement, computational models have shown that positive selection at the epithelium via the ability to metabolize specific nutrients can be a more powerful mechanism for shaping host-associated microbial communities than negative selection driven by antimicrobials 60 .…”
Section: Mechanisms Responsible For Gut Biogeographymentioning
confidence: 99%
“…MUC2 alone is coated with over 100 different O-linked glycan structures in humans 58 . These glycans differ between mice and humans 59 , and differences in complex glycan “preference” by various bacterial species is a suggested mechanism of host-specific selection of a characteristic microbiome profile. In agreement, computational models have shown that positive selection at the epithelium via the ability to metabolize specific nutrients can be a more powerful mechanism for shaping host-associated microbial communities than negative selection driven by antimicrobials 60 .…”
Section: Mechanisms Responsible For Gut Biogeographymentioning
confidence: 99%
“…95 These carbohydrates are composed of monosaccharides ranging from 2-12 monomers and are generally based on core 1-5 structures with the colon predominantly core-3. 96 There appears to be variation in the glycosylation pattern along the GI tract, with the small intestine containing core-4 highly fucosylated glycans, core-2 sulpho-lewis in the colon and blood group H/A in the cecum and ileum. 97 Sulphation of mucins generally confers resistance to degradation by both host proteases and bacterial glycosidases, and has even been implicated in conferring protection in newborns.…”
Section: -94mentioning
confidence: 99%
“…In mouse, C1GalTs, C2GnT1, C2GnT2, and C3GnT1 are expressed in the colon, whereas C1GalTs, C2GnT1, C2GnT3, and low amounts of C3GnT1 are found in the SI (58,64,66). Our analysis showed that core-1 C1GalT1 and C1GalT2 displayed the highest GT expression levels, albeit not significantly different between the two groups of mice (data not shown), in agreement with the increased proportion of core 1 structures (31,61). Significant differences in gene expression between WT and TCR␦ Ϫ/Ϫ mice were observed for core-2 C2GnT1 and core-3 C3GnT.…”
Section: Resultsmentioning
confidence: 66%
“…Mucin glycosylation is characterized by common core structures, which are variously elongated and terminated, comprising the basis for structural diversity of glycans. Two of the most common mucin-type O-glycans in mouse intestinal mucins are based on the core-1 and core-2 structures (31,61). Here C1GalT1 and C1GalT2 were most highly expressed in both groups of mice.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation